Israel-Palestine War: The Right of Self-Defense in International Law - Qureshi, Tahir; Shah, Shaeyuq Ahmad; George, Sunil; Sapre, Abhilash Arun (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
This paper examines the use of force in self-defence under customary international law, focusing on the Israel-Palestine war. It analyses explicitly whether the attacks on 7 October 2023 by Harakat al-Muqawamah al-Islamiyyah (Hamas) and Palestinian Islamic Jihad (PIJ) can be construed within the parameters of Article 51 of the United Nations Charter as an